Nitrospina-like Bacteria Are Dominant Potential Mercury Methylators in Both the Oyashio and Kuroshio Regions of the Western North Pacific - Yuya Tada; Kohji Marumoto; Akinori Takeuchi (Microbiology Spectrum, 2021)
ABSTRACT Highly neurotoxic methylmercury (MeHg) accumulates in marine organisms, thereby negatively affecting human and environmental health. Recent studies have revealed that oceanic prokaryotes harboring the hgcAB gene pair are involved in Hg methylation. Presently, little is known about the distribution and phylogeny of these genes in distinct oceanic regions of the western North Pacific. In this study, we used metagenomics to survey the distribution of hgcAB genes in the seawater columns of the subarctic Oyashio region and the subtropical Kuroshio region. The hgcAB genes were detected in the MeHg-rich offshore mesopelagic layers of both the Oyashio region, which is a highly productive area in the western North Pacific, and the Kuroshio region, which has low productivity. Comparative analysis revealed that hgcAB genes belonging to the Nitrospina-like lineage were dominant in the MeHg-rich mesopelagic layers of both regions. These results indicate that Nitrospina-like bacteria are the dominant Hg methylators in the mesopelagic layers throughout the western North Pacific. IMPORTANCE MeHg is highly neurotoxic and accumulates in marine organisms. Thus, understanding MeHg production in seawater is critical for environmental and human health. Recent studies have shown that microorganisms harboring mercury-methylating genes (hgcA and hgcB) are involved in MeHg production in several marine environments. Knowing the distribution and phylogeny of hgcAB genes in seawater columns can facilitate assessment of microbial MeHg production in the ocean. We report that hgcAB genes affiliated with the microaerophilic Nitrospina lineage were detected in the MeHg-rich mesopelagic layers of two hydrologically distinct oceanic regions of the western North Pacific. This finding facilitates understanding of the microbial Hg methylation and accumulation in seawater columns of the western North Pacific.